2020
DOI: 10.36079/lamintang.ijeste-0302.160
|View full text |Cite
|
Sign up to set email alerts
|

Teachers’ Information and Communication Technology (ICT) Skills Assessment: Basis for a Comprehensive ICT Training Program

Abstract: The study described the extent of knowledge in ICT skills of 180 teachers as a basis for a training plan in a selected schools division in Region 3. A descriptive survey method was utilized having a weighted mean and standard deviation to treat the data collected. It was concluded that the teachers displayed a proficient extent of knowledge in basic ICT skills. However, some of the skills enumerated have a low mean and were close to the adjacent group scale of the lower level of knowledge. Furthermore, they sh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 7 publications
0
2
0
Order By: Relevance
“…It is observed that there are teachers who utilize audio and video editing, which will suit to their lessons. Correspondingly, the results suggest a high level of proficiency among educators in utilizing audio and video editing tools for instructional purposes, aligning with the findings of Bayucca (2020), which emphasize the critical role of these skills in modern education. Additionally, the positive perception towards audio and video editing skills underscores their significance in enriching educational experiences and fostering multimedia-rich learning environments, as highlighted by Movitaria and Shandra (2022).…”
Section: Resultssupporting
confidence: 81%
See 2 more Smart Citations
“…It is observed that there are teachers who utilize audio and video editing, which will suit to their lessons. Correspondingly, the results suggest a high level of proficiency among educators in utilizing audio and video editing tools for instructional purposes, aligning with the findings of Bayucca (2020), which emphasize the critical role of these skills in modern education. Additionally, the positive perception towards audio and video editing skills underscores their significance in enriching educational experiences and fostering multimedia-rich learning environments, as highlighted by Movitaria and Shandra (2022).…”
Section: Resultssupporting
confidence: 81%
“…The overall mean rating is 3.84 (SD = 0.77) interpreted as Highly Literate. This result echoes the sentiments expressed in studies such as Bayucca (2020) and Hasanah and Dewi (2022), which emphasize the vital role of continuous professional development in navigating the complexities of modern education.…”
Section: Resultssupporting
confidence: 72%
See 1 more Smart Citation
“…This explains that the integration of technological advancement brings clearer perceptions about the lesson especially today. The same perspective was introduced by another study regarding the ICT skills assessment of teachers and its impact on their teaching profession [20]. Table 3 shows the ten (10) challenges enumerated by the teacher-respondents in distance learning modalities.…”
Section: Resultsmentioning
confidence: 98%
“…Teachers, acting as the most important audio-visual LR of the education milieu, should be supported by quality assured and approved LRs that will suffice the continuity of lesson's flow within the specified targeted learning competency/ies for each lesson. Teachers' ICT skills are an essential and integral component of the development of learning resources (Bayucca, 2020a). Taking this into account, public school teachers were still able to sleep and perform their religious tasks (Asio & Jimenez, 2021).…”
Section: Introductionmentioning
confidence: 99%